PENGARUH WORK LIFE BALANCE TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI (Studi pada Perawat Puskesmas Rawat Inap di Kota Semarang): Study On Puskesmas Inpatients in Semarang City - Kartika Dwi Chandra Sari (LPPM Universitas Harapan Bangsa, 2019)
The medical personnel have a great responsibility in providing optimal health care. One of the medical personnel who is directly related to the service is a nurse. Nurses are required to have a good performance, in practice, the nurse has a challenge related the duration of work hours. Sometimes the work hours didn’t proper with the compensation obtained. In this study examines the effect of work life balance on employee performance by job satisfaction as a mediating variable. This research was conducted on nurses at Puskesmas inpatient unit on Semarang with a total respondent is 86 people. The sampling method used is Census Sampling. The questionnaire consisted of 6 questions about work life balance, 4 questions about job satisfaction, and 4 questions about employee performance. Data were processed using path analysis with SPSS 22.0 statistical methods for Windows. The results of the study found that work life balance had a significant effect on employee performance. Job satisfaction does not meet the requirements to become a mediating variable because work life balance on job satisfaction does not have a significant effect, and job satisfaction on performance has no significant effect. Thus, in this study the effect of work life balance with employee performance has a direct effect